Analyzing The Protagonist Character of Elliot Anderson As Seen In The Film “Black Or White” By Mike Binder - Garwan, Hellaisna Nur 'Aini; Mitsalina, Endah; Haryadi, Rakhmat; Susanto, Ari (English Education and Literature Journal (E-Jou), 2022)
‘Black or White’ described of complains, blames, jealously, selfishness, and understanding about the family love from Elliot Anderson’s character. This research is aimed to know the character of Elliot Anderson as main character by analyzing the evidence from the dialogues and his actions in the film. To know about the character of Elliot Anderson, the writer used the descriptive qualitative method in this paper. The writer employs himself to collect the data by reading script, watching the film and marking them. The writer used the film of Black or White by Mike Binder released in 2014 by Toronto International Film Festival (TIFF). The writer focused on the dialogues of the film, and then followed by analyzing the character through conscientiousness and neuroticism of personality. In this analysis, the writer finds out that final result about the protagonist character of Elliot Anderson. Elliot Anderson is a recently widower and visible wealthy grandfather. The writer found Conscientiousness of Elliot Anderson characteristic is ambitious and neuroticism Elliot is irritable or anger, complaining person, blaming person, selfish, and jealous. It’s all happened when on one particularly bad day, in which he loses his wife, he wishes people would recognize how hard he is trying and how good his heart is and just leaving him alone in his big house with its big swimming pool and his Mexican maid to raise his young granddaughter Eloise.  Keyword: Black or White Film, Elliot Anderson, Protagonist Character